کاریگەری بنەما جوگرافیەکان لەسەر دابەشبوون و وەبەرهێنانی کشتوکاڵی لە قەزای پێنجوێن لەماوەی نێوان (٢٠١١ ـ ٢٠٢١) - علاءالدين, پ.ی.د.عطا محمد; تۆفیق, سەروەر علی (Sulaimani Journal for Humanities, 2023)
This research entitled (Geographical Principles on the Distribution and Investment of Agriculture in Penjwen District between 2011-2021) was conducted in order to familiarize with the impact of some geographical factors on the changes in cultivated area and investment of agricultural land for agricultural development Contemporary irrigation (drip) comes from the leading geographical factors on agricultural land investment in the region. The results of the study explained that agricultural land is divided into two types (demi and irrigated) with an area of (86549) dunams, of which (59990) dunams of irrigated land and (26556) dunams of irrigated land Agricultural land with an area of (60618) dunams in (2021) to be used as irrigation for summer crops, While due to the presence of suitable climatic factors, water and natural pasture resources in the region, has provided many opportunities for breeding animal species that are an important part of the agricultural sector and complement plant crops.